2020
DOI: 10.1186/s13019-020-01273-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-recovery in physical health-related quality of life one year after cardiac surgery: a prospective single Centre observational study

Abstract: Background: Recent studies show that substantial percentage of patients experienced worsening of health related quality of life (HRQoL) 1 year after cardiac surgery. The aim of this study is to identify risk factors that interfere with improvement of HRQoL. Methods: From December 2015 till July 2017 a prospective single centre observational study was carried out in 1920 patients participated who underwent non-salvage cardiac surgery. All patients were requested to complete a Short Form 36 (SF-36) questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Symptom experience was identified as a significant factor that affects the PCS score, and this finding is in agreement with the findings of previous studies, which found that symptoms such as depression, anxiety 12 , postoperative adverse effects 9 , angina, and shortness of breath 11 , 19 decreased the PCS score of post-CABG patients. The more serious the post-CABG symptom experience, the more likely it is that the uncertainty and supportive care needs will increase 35 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Symptom experience was identified as a significant factor that affects the PCS score, and this finding is in agreement with the findings of previous studies, which found that symptoms such as depression, anxiety 12 , postoperative adverse effects 9 , angina, and shortness of breath 11 , 19 decreased the PCS score of post-CABG patients. The more serious the post-CABG symptom experience, the more likely it is that the uncertainty and supportive care needs will increase 35 .…”
Section: Discussionsupporting
confidence: 91%
“…This outscoring of the post-CABG PCS by the post-CABG MCS is attributable to the limitation of everyday physical activity and the decreased treatment compliance rate after CABG 11 , 25 , which can also negatively affect the MCS 7 . One-fifth of CAD patients have a constantly low PCS score after CABG 9 , which highlights the need for a follow-up study to screen the high-risk group with a persistently low PCS score and follow the changing trends of PCS scores from the immediate post-CABG timepoint up to 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a subsequent assessment at three months after discharge has added value in the identification of long-term non-recovery, and can be a trigger for further rehabilitation. This adds to the existing literature, since pre-ICU data on quality of life and physical functioning comes from studies in the elective surgical group [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of people around the world who receive cardiac surgery is increasing [1][2][3][4] . Even a successful cardiac surgery cannot guarantee that patients completely restore physical functions and quality of life (QoL) [5][6][7] . Previous studies have found that even in patients undergoing high-risk elective cardiac surgeries with a good prognosis and a short hospital stay, acute muscle loss occurs due to the imbalance between muscle atrophy and the death of muscle cells [8] .…”
Section: Introductionmentioning
confidence: 99%